Prevalence Truancy is Associated with Attitude, Family and School Environment Factors - et. al., Mohd Haizam Saudi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Truancy is a major issue that often plagues a country's education system. This phenomenon is also the highest contributor to student misconduct cases, especially in Malaysia. The purpose of this study is to identify the relationship between three main factors, namely student attitudes, family relationships and school environment in influencing truancy among students. A total of 148 students consisting of upper secondary school students in an east coast secondary school in Peninsular Malaysia was selected as respondents in this study. The results of this analysis process show that factors such as student attitudes, family relationships and school environment have a significant relationship with truancy among students. Schools in particular and the ministry in general should make these factors the main agenda in formulating programs and activities to curb this issue from continuing to plague the national education system. In fact, the role of parents is no exception in efforts to curb these symptoms from continuing to occur among students at school.